PENGARUH KEKERASAN PADA CYBERBULLYING TERHADAP PERILAKU MASYARAKAT PADA MASA COVID-19: Indonesia - Andi Kurniawan, Ricky; Kelvin; Anderson, Kevin; Djayadhinata; Olwin; Saputra, Indra (J-ENSITEC (Journal of Engineering and Sustainable Technology), 2022)
The purpose of this study was to determine the condition of cyberbullying that happened the city of Batam, especially during the ongoing Covid-19 pandemic. The types of research we use are qualitative and quantitative. This research was conducted with many respondents with a total of 250 respondents. The sampling technique used is the Cluster & Stratified Random Sampling technique. The results showed that 30.8% often experienced or encountered cases of Cyberbullying and 45.2% had experienced or encountered cases of Cyberbullying. From the research, 62.8% experienced it in the school environment and 37.2% experienced it outside the school environment. This research can be a reference for readers in finding and determining the level of Cyberbullying cases in Batam city and how to handle them.